MaxEnt-Simulated Site Suitability Model for Adlai (Coix lacryma-jobi. L.) in Bukidnon, Philippines - Joseph Paquit; Jason Parlucha; Garry Marapao (agriTECH, 2022)
To create a baseline and projected site suitability models for Adlai and assess the effects of climate change on the distribution of the species, 52 species occurrence points (SOPs) and 14 bioclimatic variables were used. Subsequently, purposive sampling was adopted to collect SOPs, while bioclimatic variables were obtained from a credible online source. The results showed that 245,980 hectares in the province are suitable for species based on the model. To determine the impact of climate change, the projected suitability modeled over 30 years was used, showing an increase from 245,980 hectares to 391,872, an increase of 145,892 hectares. Most of the projected suitable areas are in the southern part where some towns have almost 100% suitability coverage. The prediction accuracy of the model was excellent at 92% based on the Receiver Operating Characteristic-Area Under Curve (ROC-AUC). The bioclimatic variable with the most important contribution is AP12 (annual precipitation) which obtained 24.74%. The information generated in this research is essential for interested sectors in planning, targeting, and prioritizing strategic areas for Adlai investment programs.